The Influence of Perceived Organizational Support and Trust in Supervisor on Organizational Citizenship Behavior with Job Satisfaction as a Mediating Variable - Erik Ferdiyan Kurnia Harun; Nurul Hermina (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to analyze the effect of perceived organizational support and trust in supervisors on organizational citizenship behavior (OCB), with job satisfaction as a mediating variable. The population in this study consists of permanent employees at PT PLN (Persero) UP3 Cimahi. A purposive sampling technique was employed. The research method used is quantitative with a descriptive-verificative approach. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). A total of 115 respondents were selected using a purposive sampling technique. The results show that perceived organizational support and trust in supervisors have a positive and significant effect on job satisfaction. Furthermore, job satisfaction has a significant effect on OCB and acts as a significant mediating variable in the relationship between perceived organizational support and trust in supervisors on OCB. These findings imply that strengthening organizational support and trust-based leader-subordinate relationships can enhance employees’ extra-role contributions to the organization.